2023
DOI: 10.1002/jbt.23319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of ginsenoside Rg1 on CPF‐induced brain injury in mice via PI3k/AKT pathway

Abstract: Organophosphorus pesticides (OPs) have long been used extensively on agricultural land and can lead to significant improvements in crop yields. Due to occupational exposure, humans are exposed to pesticides through dermal contact, inhalation, and ingestion. The effects of OPs on the organism are currently studied for their effects on livers, kidneys, hearts, blood indicators, neurotoxicity, and teratogenic, carcinogenic, and mutagenic effects, while studies in the direction of brain tissue damage have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The results our previous studies suggested that CPF-induced ROS accumulation mediates oxidative stress damage and interferes with mitochondrial membrane potential homeostasis and cell function [37]. Wang et al [56] showed that ROS accumulation in RAW264.7 cells is an upstream signal to mobilize the NF-κB pathway and causes the overproduction of inflammatory factors (TNF-α, IL-1β).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results our previous studies suggested that CPF-induced ROS accumulation mediates oxidative stress damage and interferes with mitochondrial membrane potential homeostasis and cell function [37]. Wang et al [56] showed that ROS accumulation in RAW264.7 cells is an upstream signal to mobilize the NF-κB pathway and causes the overproduction of inflammatory factors (TNF-α, IL-1β).…”
Section: Discussionmentioning
confidence: 96%
“…Meyer) is widely distributed in northeast China. Its functions include invigorating vitality, the spleen and the lungs; calming the mind; and improving the brain [36,37]. Ginseng stem-and-leaf saponins are the main active components of ginseng and have antioxidant [38], anti-inflammatory [39], anti-apoptotic [40] and protective effects on the nervous system.…”
Section: Introductionmentioning
confidence: 99%